2013
DOI: 10.1007/s00391-013-0522-8
|View full text |Cite
|
Sign up to set email alerts
|

Therapieergebnisse und Anwendungssicherheit von Symphytum-Herba-Extrakt-Creme in der Behandlung von Dekubitus

Abstract: In an open, prospective use study, 161 patients with 198 decubitus ulcers (pressure ulcers, ITT population) in stages II and III were treated with the topical preparation symphytum herb extract cream. The bandages with the cream were changed every 2-3 days. The primary parameters evaluated were the area of the sore and the depth of the wound (planimetrically in mm). In all, 151 patients with a total of 184 pressure sores (PP population) were included and received treatment over a period of 4 weeks in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…Only two cases of local irritation were stated post-treatment period. Therefore, this study confirmed that comfrey extract is highly effective in pressure ulcers treatment and also it shows excellent skin compatibility in the case of open sores [163]. However, taking into consideration the general rule, more human studies are needed to justify both the efficacy and safety of comfrey extracts in treating skin problems.…”
Section: Clinical Effectiveness Of Symphytum Species In Humanssupporting
confidence: 66%
“…Only two cases of local irritation were stated post-treatment period. Therefore, this study confirmed that comfrey extract is highly effective in pressure ulcers treatment and also it shows excellent skin compatibility in the case of open sores [163]. However, taking into consideration the general rule, more human studies are needed to justify both the efficacy and safety of comfrey extracts in treating skin problems.…”
Section: Clinical Effectiveness Of Symphytum Species In Humanssupporting
confidence: 66%
“…A study by Stepan et al (2013) assessed the potential of Symphytum Herba extract cream on pressure ulcers, decubitus bedsores, with bandages containing the cream changed every 2–3 days. All ulcers in this study were treated with Symphytum Herba extract cream, with no inclusion of an untreated control group [ 51 ]. Symphytum Herba extract cream is said to contain Symphytum × uplandicum Nyman, with allantoin reported as one of the major components responsible for the pharmacological effects, with the chemical structure depicted in Figure 5 ; it is typically referred to as Comfrey and is a perennial plant [ 51 , 52 ].…”
Section: Pressure Ulcersmentioning
confidence: 99%
“…All ulcers in this study were treated with Symphytum Herba extract cream, with no inclusion of an untreated control group [ 51 ]. Symphytum Herba extract cream is said to contain Symphytum × uplandicum Nyman, with allantoin reported as one of the major components responsible for the pharmacological effects, with the chemical structure depicted in Figure 5 ; it is typically referred to as Comfrey and is a perennial plant [ 51 , 52 ]. The study had a large patient cohort, consisting of 151 participants involved in the study until its completion, with 184 pressure ulcers present across the participants.…”
Section: Pressure Ulcersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ärzte und Patienten stuften den Behandlungserfolg gemessen an einer verbalen Rating-Skala 0-4 zu 90 % und an einer visuellen Analogskala 0-100 zu 88 % als erfolgreich ein (PP-Kollektiv). Bei 2 Patienten kam es zu einer lokalen Hautreizung [43].…”
Section: Bei Dekubitusgeschwürenunclassified